Ensino de contato visual, imitação e ecoico a crianças com microcefalia - Ciarlini, Nathalie Cerqueira (2019)
The number of reports of children born with or suspected to be born with microcephaly in Brazil, increased considerably in 2015. This increase is being associated with the temporal entry of the Zika Virus into the country. Laboratory and epidemiological studies have already confirmed this relationship between the births of children with malformation and the women infected by the virus during pregnancy. The severity of the sequela in these children varies case to case, so a specific treatment to treat these malformations does not exist yet. What does exist are support actions being taken to help treat the illness. These support actions were advocated by the Single Health System (SUS). It is estimated that about 90% of these children may present some type of mental retardation, delay in neuropsychomotor development, hearing problems, as well as visual and speech problems. Realizing the gravity of the situation, the Ministry of Health began to treat the case as an emergency to public health and set out to orient people on microcefalia through a multiprofessional format. The objective was to minimize neuropsychomotor disorders, as well as minimize harms a child can face in socialization, bonding and welcoming. The work focused on the area of language, with the objective of teaching child development prerequisites like visual contact under instructional control, imitation and verbal eco-operant. These skills were taught to four children whose ages ranged from 2 years and 2 months to 2 years and 4 months. They had also all been diagnosed with microcephaly and attended a specialized clinic in a capital of Northeastern Brazil. The teaching of these prerequisites was based on the fact that the P showed absence of such repertoires and because they are essential for the teaching of other skills. Preference evaluations of the Pareto type and Single Stimulus were carried out with each participant and after this phase, the teaching was programmed and structured, so each target behavior could be taught, by means of Instructions for Discrete Attempts. In the baseline phase, since the P presented a performance rate of less than 50% of target hits, visual and physical cues were used throughout the procedure. The four P reached the learning criterion for visual contact under instructional control so, to replicate this success, the behavior during learning was used as a prerequisite for the following children. In the teaching of imitation, the three P reached established learning criterion and one P had to be disconnected from this phase, since it presented a lot of motor agitation. In the Ecoico operant teaching, a P reached criterion for a model and started teaching with a second model. The other three participants did not meet the criteria. The results suggest that the teaching procedure in this format was effective for the installation of a previously absent behavior: that of visual contact under instructional control. This behavior remained during the other phases of teaching. The research was a start for all the future researches that look into teaching practices that enable the development of these children.